know some rules for modular arithmetic expressions, for example,
- $A+B=C\implies ((A\bmod M) + (B\bmod M))\bmod M = C\bmod M$.
2.$A\times B=C\implies $((A\bmod M)\times (B\bmod M))\bmod M = C\bmod M$.
($A$, $B$, $C$, and $M$ are just constant arbitrary integers)
But I did not understand the following one $$A - B = C \implies ( (A\bmod M)-(B\bmod M)+kM)\bmod M = C\bmod M$$ for some value $k$.
I am interested because, as I know, such methods are used in computing hash values of strings and generally related with string search methods. My question is, what does $k$ do in this case? Can we use arbitrary value of $k$? or how to calculate which value of $k$ is relevant for such calculation? Thanks a lot.